174k views
2 votes
Two equivalent expressions are shown in the equation where a and b are both integers. a(8x - 7) = b + 48x The value of a is The value of b is

User Bertilio
by
7.5k points

1 Answer

4 votes

EXPLANATION

Given the expressions:

(1) a(8x - 7) = b + 48x

Dividing both sides by 8x-7:

a= (b+48x)/(8x-7)

Now, considering the first expression and subtracting both sides by -48x

a(8x - 7) -48x = b

Applying the distributive property:

8ax -7a - 48x = b

Grouping like terms:

(8a-48)x - 7a = b

Switching sides:

b = (8a-48)x - 7a

User Herm
by
7.1k points